Propofol Inhibits the Activation of p38 through Up-Regulating the Expression of Annexin A1 to Exert Its Anti-Inflammation Effect - Tang, Jing (Public Library of Science, 2011)
Inflammatory response is a kind of nonspecific immune response, with the central link of vascular response, which is mainly manifested by changes in neutrophils and vascular endothelial cells. In recent years, the in vivo and in vitro role of intravenous anesthetic propofol in inhibiting inflammatory response has been attracting more and more attention, but the anti-inflammatory mechanisms of propofol for mononuclear cells still remain undefined. In this study, proteomics analysis was applied to investigate protein expression profile changes in serum mononuclear cells following intervention of rats with endotoxemia using propofol. After two-dimensional electrophoresis and mass spectrometric identification, it has been found that the protein Annexin A1 was up-regulated in the propofol intervention group. Annexin A1 is a glucocorticoid-dependent anti-inflammatory protein. After detection using ELISA and Western blot assays, it has also been found that propofol can not only promote the expression of Annexin A1, but also inhibit the phosphorylation level of p38 and release of inflammatory factors (IL-1β, IL-6 and TNF-α) in rats with endotoxemia. In order to further determine the role of up-regulated expression of Annexin A1 in anti-inflammation of propofol, this gene was silenced in vitro in human THP-1 cells, to detect the phosphorylation status of p38 and release of inflammatory factors. The results show that Annexin A1 can negatively regulate phosphorylation of p38 and release of IL-1β, IL-6 and TNF-α in THP-1 cells following propofol intervention and lipopolysaccharide (LPS) stimulation. Our results clearly indicate that propofol can up-regulate Annexin A1 to inhibit the phosphorylation level of p38 and release of IL-1β, IL-6 and TNF-α, so as to inhibit inflammatory response. Therefore, it can be speculated that Annexin A1 might be the key signaling protein in the in vivo and in vitro anti-inflammatory mechanisms of propofol.